2011
DOI: 10.1186/1471-2180-11-65
|View full text |Cite
|
Sign up to set email alerts
|

Lateral gene transfer of streptococcal ICE element RD2 (region of difference 2) encoding secreted proteins

Abstract: BackgroundThe genome of serotype M28 group A Streptococcus (GAS) strain MGAS6180 contains a novel genetic element named Region of Difference 2 (RD2) that encodes seven putative secreted extracellular proteins. RD2 is present in all serotype M28 strains and strains of several other GAS serotypes associated with female urogenital infections. We show here that the GAS RD2 element is present in strain MGAS6180 both as an integrative chromosomal form and a circular extrachromosomal element. RD2-like regions were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 42 publications
1
49
0
1
Order By: Relevance
“…There is strong evidence that RD2 originated in GBS and was acquired by GAS through horizontal gene transfer. It has been proposed that genes carried within RD2 might contribute to both GAS and GBS pathogenicity (28,29). Supporting this, AspA has been shown to facilitate GAS biofilm formation on salivary pellicle (25), respiratory infection, and evasion of phagocytosis (30).…”
mentioning
confidence: 61%
“…There is strong evidence that RD2 originated in GBS and was acquired by GAS through horizontal gene transfer. It has been proposed that genes carried within RD2 might contribute to both GAS and GBS pathogenicity (28,29). Supporting this, AspA has been shown to facilitate GAS biofilm formation on salivary pellicle (25), respiratory infection, and evasion of phagocytosis (30).…”
mentioning
confidence: 61%
“…In addition to CIP, RD2 encodes several proteins with predicted secretion signal sequences, among which the R28 protein that has been implicated in host-pathogen interactions (39). Interestingly, in GAS this region is present in all serotype M28 strains and in strains of other serotypes associated with maternal-fetal urogenital infections (40,41). In the case of GBS, analysis of the 373 genomes present in the NCBI database revealed 80 cip + strains mainly belonging to the hypervirulent type III ST-17, ST-23, and to the bovine ST-61-67.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several studies showed or strongly suggested that at least some ssDNA-transferring ICEs may be capable of extrachromosomal replication as plasmid-like molecules in both Gram-positive and Gramnegative bacteria (91,95,96,97).…”
Section: Replication Of Icebs1mentioning
confidence: 99%